2017
DOI: 10.5539/ass.v13n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment and Rewards in Thailand, with Comparison between University Graduates and Others

Abstract: This study investigates the relationship between extrinsic, intrinsic and social rewards, and the organizational commitment of 6,911 employees who work for 13 Japanese companies in Thailand. Hierarchical regression analysis revealed that variables included to measure extrinsic, social and intrinsic rewards were strongly related to organizational commitment. These findings suggest that the antecedents of organizational commitment in the Japanese companies in Thailand are different from those in the other kind o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Recent research by Kokubun (2017a;2017b) confirmed such correlations in setting of Thailand and Malaysia using the same questions, too. Accordingly, the researcher expects the similar association between the variables of reward and OC described below because these countries and China share similarities in geographical and cultural spheres (e.g., collectivism, high-power distance, etc.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…Recent research by Kokubun (2017a;2017b) confirmed such correlations in setting of Thailand and Malaysia using the same questions, too. Accordingly, the researcher expects the similar association between the variables of reward and OC described below because these countries and China share similarities in geographical and cultural spheres (e.g., collectivism, high-power distance, etc.…”
Section: Methodsmentioning
confidence: 71%
“…intrinsic rewards, extrinsic rewards and social rewards. In previous research, intrinsic rewards comprised autonomy, training provision and role clarity; extrinsic rewards included benefit satisfaction and fatigue; social rewards contained supervisor support and co-worker support (e.g., Kokubun, 2017a). Porter and Lawler (1968) defined intrinsic rewards as the satisfaction that a person derives from doing the job and extrinsic rewards as tangible benefits obtained as a result of doing the job, such as pay and promotions.…”
Section: Organizational Rewards In Chinamentioning
confidence: 99%
“…Among them, Hypothesis 9, 10, 11 and 13 are common with those of previous survey in Thai setting (Kokubun, 2017a). However, Hypothesis 8 and 12 are different: In previous research (Kokubun, 2017a), benefit satisfaction had stronger effect towards OC in University graduates than in 'others'; autonomy had equal effect towards OC between university graduates and 'others'.…”
Section: The Level Of Education and Comparative Importance Of Rewardsmentioning
confidence: 65%
“…Recent research by Kokubun (2017a;2017c) confirmed such correlations in setting of Thailand, Malaysia and China using the same questions, too. Accordingly, the researcher expects the similar association between the variables of reward and OC described below because these countries and Vietnam share similarities in geographical and cultural spheres (e.g., collectivism, high-power distance, etc.…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation